2006
DOI: 10.1002/pi.2098
|View full text |Cite
|
Sign up to set email alerts
|

Vapor‐based polymer coatings for potential biomedical applications

Abstract: Over the last decade, biology and biotechnology have witnessed an extraordinary development spanning genomics, proteomics, and metabolics. This progress was so rapid and definite that it not only changed the face of modern biology, but indeed altered the way day‐to‐day business is done in biology and related fields. This scientific advancement came with a need for concurrent technological advances. In this context, the ability to interface sophisticated devices with relevant biological microenvironments has em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
120
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 72 publications
0
120
0
Order By: Relevance
“…This designation is the highest level of biocompatibility possible for polymers permitting its use in applications where long-term implantation is required. Its biocompatibility, biostability, low cytotoxicity and resistance against hydrolytic degradation [1,12,13] have resulted in increasing popularity of Parylene C in micro-and nano-fabricated devices for microfluidic and bioMEMS applications. For example, Parylene C-based devices have been demonstrated as platforms for neuronal growth [14][15][16] and in implantable neuronal probes [17].…”
Section: Introductionmentioning
confidence: 99%
“…This designation is the highest level of biocompatibility possible for polymers permitting its use in applications where long-term implantation is required. Its biocompatibility, biostability, low cytotoxicity and resistance against hydrolytic degradation [1,12,13] have resulted in increasing popularity of Parylene C in micro-and nano-fabricated devices for microfluidic and bioMEMS applications. For example, Parylene C-based devices have been demonstrated as platforms for neuronal growth [14][15][16] and in implantable neuronal probes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Conformal polymer films on membrane templates were achieved by CVD with PPXC (trade name parylene C) (Lahann 2006;Gazicki-Lipman 2007). The polymer layer thickness amounted to »1 mm (SEM: »1.1 mm; surface profilometer: »0.8 mm) (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The CVD process lacks catalysts, solvents or side products (i.e., negligible amounts of leachables, which could raise potential toxicological concerns) during polymer film synthesis (Alf et al 2010;Coclite et al 2013) and has, therefore, found broad scope of potential applications in the biomedical field (Lahann 2006). As an example, parylene is commonly utilized during the fabrication of several medical implants CUSTOMIZED VIBRATING-MEMBRANE NOZZLES v (e.g., bone fixation [Cieslik et al 2012] and coronary stents [Wolf et al 2008]).…”
Section: Resultsmentioning
confidence: 99%
“…Parylene C was selected as the channel and cell/tissue interface material for its excellent material properties, compatibility with micro-and nanofabrication processes, and its biocompatibility with both short-and long-term growth of cells/tissues [10][11][12]. Furthermore, Parylene C is transparent and allows convenient observation of channel contents by light and fluorescence microscopy.…”
Section: Designmentioning
confidence: 99%